2009
DOI: 10.1111/j.1600-0854.2009.00980.x
|View full text |Cite
|
Sign up to set email alerts
|

Live Cell Multicolor Imaging of Lipid Droplets with a New Dye, LD540

Abstract: A lipophilic dye based on the Bodipy fluorophore, LD540, was developed for microscopic imaging of lipid droplets. In contrast to previous lipid droplet dyes, it can spectrally be resolved from both green and red fluorophores allowing multicolor imaging in both fixed and living cells. Its improved specificity, brightness and photostability support live cell imaging, which was used to demonstrate by two-color imaging lipid droplet motility along microtubules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
179
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 233 publications
(187 citation statements)
references
References 18 publications
(21 reference statements)
2
179
0
Order By: Relevance
“…not requiring sophisticated proteomics to quantify lipases) monitoring of lipid esterases using a fluorescent readout. Although the quantitative relationship between fluorescence and protein levels has not been determined in detail in this study, imaging of THL-alk1 adducts in cells with larger dimensions (such a eukaryotic cells) will help understand better the spatial distribution of enzymes involved in the dynamics of lipid droplets (47)(48)(49). In addition, THL-alk1 and its closely related derivatives could be useful in other innovative approaches for the systematic determination of protein-small molecule interactions (50 -52).…”
Section: Discussionmentioning
confidence: 99%
“…not requiring sophisticated proteomics to quantify lipases) monitoring of lipid esterases using a fluorescent readout. Although the quantitative relationship between fluorescence and protein levels has not been determined in detail in this study, imaging of THL-alk1 adducts in cells with larger dimensions (such a eukaryotic cells) will help understand better the spatial distribution of enzymes involved in the dynamics of lipid droplets (47)(48)(49). In addition, THL-alk1 and its closely related derivatives could be useful in other innovative approaches for the systematic determination of protein-small molecule interactions (50 -52).…”
Section: Discussionmentioning
confidence: 99%
“…Laurdan generalized polarization Besides lipid probes for the plasma membrane, there are also some tools to probe other lipidic environments in the cell, such as lipid droplets (Thiele and Spandl 2008). New fluorescent lipids were developed to visualize the intracellular and membrane lipids in their native environment without any external fluorescent labels (Kuerschner et al 2005;Spandl et al 2009). …”
Section: Fluorescent Probes To Study Lipid Dynamicsmentioning
confidence: 99%
“…New fluorescent lipids were developed to visualize the intracellular and membrane lipids in their native environment without any external fluorescent labels (Kuerschner et al 2005;Spandl et al 2009). …”
Section: Fluorescent Probes To Study Lipid Dynamicsmentioning
confidence: 99%
“…and in A. thaliana (the current work) as well as in COS7 fibroblasts [11], it has been shown that diacylglycerol acyltransferase 2 (DGAT2), an enzyme involved in the final stage of triacylglycerol synthesis, was present at the surfaces of lipid bodies, which may confirm the suggestion that lipid synthesis also occurs on them. Microtubules and lipid bodies in close contact have been observed in different animal cells in connection with lipid bodies' motion [28][29][30]. On the other hand, the observations of Pacheco et al [19] implicate microtubule contribution to lipid synthesis.…”
Section: Resultsmentioning
confidence: 81%